Bronchoalveolar sublineage specification of pluripotent stem cells: effect of dexamethasone plus cAMP-elevating agents and keratinocyte growth factor - Katsirntaki, Katherina-Elpida; Dürr, Julia; Schubert, Susanne C.; Mall, Marcus A. (Tissue engineering, 2015)
Respiratory progenitors can be efficiently generated from pluripotent stem cells (PSCs). However, further targeted differentiation into bronchoalveolar sublineages is still in its infancy, and distinct specifying effects of key differentiation factors are not well explored. Focusing on airway epithelial Clara cell generation, we analyzed the effect of the glucocorticoid dexamethasone plus cAMP-elevating agents (DCI) on the differentiation of murine embryonic and induced pluripotent stem cells (iPSCs) into bronchoalveolar epithelial lineages, and whether keratinocyte growth factor (KGF) might further influence lineage decisions. We demonstrate that DCI strongly induce expression of the Clara cell marker Clara cell secretory protein (CCSP). While KGF synergistically supports the inducing effect of DCI on alveolar markers with increased expression of surfactant protein (SP)-C and SP-B, an inhibitory effect on CCSP expression was shown. In contrast, neither KGF nor DCI seem to have an inducing effect on ciliated cell markers. Furthermore, the use of iPSCs from transgenic mice with CCSP promoter-dependent lacZ expression or a knockin of a YFP reporter cassette in the CCSP locus enabled detection of derivatives with Clara cell typical features. Collectively, DCI was shown to support bronchoalveolar specification of mouse PSCs, in particular Clara-like cells, and KGF to inhibit bronchial epithelial differentiation. The targeted in vitro generation of Clara cells with their important function in airway protection and regeneration will enable the evaluation of innovative cellular therapies in animal models of lung diseases.